2017
DOI: 10.1002/lary.26448
|View full text |Cite
|
Sign up to set email alerts
|

Incidental parathyroidectomy during thyroidectomy increases the risk of postoperative hypocalcemia

Abstract: 4. Laryngoscope, 127:2194-2200, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
65
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(75 citation statements)
references
References 22 publications
6
65
4
Order By: Relevance
“…Finding a parathyroid gland in postoperative thyroidectomy specimen without any intention to do parathyroidecomy is known as incidental parathyroidectomy (IP). The incidence ranges between 6.4% and 31.1% [5][6][7][8][9][10][11]. Over the past decades, standardization of the thyroidectomy technique and advances in perioperative management have led to significant reduction in the overall morbidity [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding a parathyroid gland in postoperative thyroidectomy specimen without any intention to do parathyroidecomy is known as incidental parathyroidectomy (IP). The incidence ranges between 6.4% and 31.1% [5][6][7][8][9][10][11]. Over the past decades, standardization of the thyroidectomy technique and advances in perioperative management have led to significant reduction in the overall morbidity [5].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, standardization of the thyroidectomy technique and advances in perioperative management have led to significant reduction in the overall morbidity [5]. Although IP is considered a minor finding in final histopathology and not a life-threatening complication of thyroid surgery, it is important for the thyroid surgeon to be able to identify factors that increase the risk for IP during thyroidectomy and exercise appropriate caution in those patients [6]. Preoperative diagnosis, type of operation, and presence of nodal metastases may influence the likelihood of IP; however, there is no unanimity of risk factors agreed upon in the literature [7].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical trauma, devascularization, extent of surgery, and incidental parathyroidectomy (IP) have been found to affect postoperative hypocalcemia. [ 2 , 4 , 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that pathology type, procedure extent, reoperation and central neck dissection are risk factors of IP in thyroidectomy. [ 4 , 8 ] However, these relationships have not been found in all studies. [ 9 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…The importance of preserving well-vascularized glands has been reconfirmed by recent studies using indocyanine green fluorescence angiography that showed PTH levels on postoperative day 1 were normal in all patients who had at least one well vascularized parathyroid gland and none of these patients required treatment for hypoPT [ 3 ]. In addition, inadvertent removal of the parathyroid glands during thyroid surgery is reported to occur in as little as 6% of patients [ 4 ] or as high as 25% [ 2 , 5 ]. More recently, intraoperative infrared imaging has been used to identify parathyroid glands based on their autofluorescence [ 6 ] but it is yet to be demonstrated whether routine use of this technique will decrease the risk of postthyroidectomy hypoPT.…”
Section: Introductionmentioning
confidence: 99%